2017
DOI: 10.1103/physreve.96.033001
|View full text |Cite
|
Sign up to set email alerts
|

Size scaling of failure strength with fat-tailed disorder in a fiber bundle model

Abstract: We investigate the size scaling of the macroscopic fracture strength of heterogeneous materials when microscopic disorder is controlled by fat-tailed distributions. We consider a fiber bundle model where the strength of single fibers is described by a power law distribution over a finite range. Tuning the amount of disorder by varying the power law exponent and the upper cutoff of fibers' strength, in the limit of equal load sharing an astonishing size effect is revealed: For small system sizes the bundle stre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…To investigate the evolution of fracture processes leading to ultimate failure, we use a generic fiber bundle model (FBM) which has proven successful in reproducing both the constitutive response and the intermittent bursting dynamics of heterogeneous materials on the macro-and microscales, respectively 60,61 . The model is composed of N parallel fibers, similar to a rope, which have a linearly elastic behavior.…”
Section: Disorder Driven Transition Between Brittle Quasi-brittle Amentioning
confidence: 99%
“…To investigate the evolution of fracture processes leading to ultimate failure, we use a generic fiber bundle model (FBM) which has proven successful in reproducing both the constitutive response and the intermittent bursting dynamics of heterogeneous materials on the macro-and microscales, respectively 60,61 . The model is composed of N parallel fibers, similar to a rope, which have a linearly elastic behavior.…”
Section: Disorder Driven Transition Between Brittle Quasi-brittle Amentioning
confidence: 99%
“…We could explain this interesting effect based on the extrem order statistics of the strength of single fibers, i.e. we pointed out that the bundle strength increases until the strongest fiber dominates the ultimate failure of the system [38]. For sufficiently small systems, at high cutoffs ε max , the strongest fiber can be so strong that it can keep the entire load on the system.…”
Section: Fiber Bundle Model With Fat-tailed Disordermentioning
confidence: 98%
“…In Ref. [38] we have shown that for fat tailed distri- Fig. 11 is presented in such a way that along the horizontal axis the system size N is rescaled with λ µ .…”
Section: Size Dependent Avalanche Statisticsmentioning
confidence: 99%
“…Note that the fracture strength σ c and ε c of FBMs depend on the system size N even in the mean field limit [27][28][29]. Although the convergence is rapid, strictly speaking the above expressions give the bundle strength in the limit of infinite system size.…”
Section: Macroscopic Responsementioning
confidence: 99%